Studying Socio-economic and Ecological Transformations in Vietnam: An Interdisciplinary Approach - Khanh, Nguyen Van (VNU Journal of Science: Policy and Management Studies, 2019)
From the 1930s to the mid-twentieth century, a number of interdisciplinary studies on the relationship among humans and natural and social environments (e.g. Human Ecology, Environmental Sociology, Social Ecology) emerged. This is a result of the integration of disciplines derived from multiple approaches in scientific research. To date, these interdisciplinary studies have provided important premises for the formation of new perspectives, including those on socio-economic and ecological transformations. This paper discusses the newly-formed perspectives on socio-economic and ecological transformations and the issues relating to the development of these research perspectives in Vietnam.